ANALISIS PENERAPAN PERATURAN PEMERINTAH NOMOR 47 TAHUN 2012 TERHADAP TANGGUNGJAWAB SOSIAL PERUSAHAAN BUMN SEBAGAI SALAH SATU PELAKU USAHA DALAM PEREKONOMIAN - Tami Rusli (Universitas Bandar Lampung (UBL), 2020)
Social and environmental responsibility (TJSL) is one of the limited liability companies in carrying out their role in order to contribute to the development of the national economy. Article 74 paragraph (1) of the Law on Junto PP Number 47 of 2012 stipulates that,